The Role of Notaries in Ensuring Legal Certainty in Acquiring Land Rights Based on Inheritance in Indigenous Communities - Leriana, Helda; Djaja, Benny (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The acquisition of land rights through inheritance in customary law communities represents the continued existence of indigenous legal systems that are still recognized within Indonesia's national legal framework. However, such transfers are often undocumented within the national land registration system, resulting in legal uncertainty. In this context, notaries play a strategic role as public officials authorized to draw up authentic deeds that provide legal certainty and protection for such acquisitions. This study aims to analyze the role of notaries in ensuring legal certainty in the inheritance-based acquisition of land rights in customary law communities, as well as to identify challenges and formulate effective strategies within notarial practice. This research employs a normative and empirical juridical approach by examining statutory regulations, legal doctrines, and conducting interviews with notaries and traditional leaders. The findings reveal that notaries not only perform formal-administrative functions but also engage substantively in verifying the validity of inheritance claims based on customary law and formalizing them into legally recognized deeds. The primary challenges include the lack of written evidence, discrepancies between legal systems, and limited coordination between indigenous communities and land administration authorities. Therefore, a synergistic approach is required among notaries, customary leaders, and state institutions to develop a system of proof that accommodates customary legal realities while upholding the principle of legal certainty.